2020
DOI: 10.1101/2020.07.28.225151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Pluripotent Stem Cell-Derived Neural Cells and Brain Organoids Reveal SARS-CoV-2 Neurotropism

Abstract: SUMMARYNeurological complications are common in patients with COVID-19. While SARS-CoV-2, the causal pathogen of COVID-19, has been detected in some patient brains, its ability to infect brain cells and impact their function are not well understood, and experimental models using human brain cells are urgently needed. Here we investigated the susceptibility of human induced pluripotent stem cell (hiPSC)-derived monolayer brain cells and region-specific brain organoids to SARS-CoV-2 infection. We found modest nu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 85 publications
(85 reference statements)
5
36
0
1
Order By: Relevance
“…Thus, unlike recent reports where SARS-CoV-2 was added directly to neuroglial organoids lacking brain-barrier cells 2125 , we do not observe significant virus invasion in cortex parenchymal cells. On the other hand, SARS-CoV-2 infection of the CSF-barrier forming choroid plexus and meninges corroborates recent in vitro, in silico , CSF, and postmortem case studies suggesting CNS barrier cells can support productive infection at relatively low titers 5,23,24,42,43 . We note however that this absence of detectable SARS-CoV-2 neuroinvasion does not exclude its possibility.…”
Section: Sars-cov-2 Accumulation In Barrier Cells Stimulates Inflammasupporting
confidence: 80%
See 2 more Smart Citations
“…Thus, unlike recent reports where SARS-CoV-2 was added directly to neuroglial organoids lacking brain-barrier cells 2125 , we do not observe significant virus invasion in cortex parenchymal cells. On the other hand, SARS-CoV-2 infection of the CSF-barrier forming choroid plexus and meninges corroborates recent in vitro, in silico , CSF, and postmortem case studies suggesting CNS barrier cells can support productive infection at relatively low titers 5,23,24,42,43 . We note however that this absence of detectable SARS-CoV-2 neuroinvasion does not exclude its possibility.…”
Section: Sars-cov-2 Accumulation In Barrier Cells Stimulates Inflammasupporting
confidence: 80%
“…There are, however, limitations to consider given the unique logistical circumstances of a pandemic. With most postmortem COVID-19 brain tissue immediately fixed 42 or not handled with snRNA-seq studies in mind for safety and regulatory reasons, there is a lack of the high-quality tissue necessary for such studies 21,23,24 . This has precluded larger study cohorts that could be more representative of COVID-19 patients as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human-induced pluripotent stem cells (hiPSCs) have emerged as valuable in vitro platforms to model human brain development and diseases for which human cells and tissues are not easily accessible ( Takahashi et al., 2007 ; Yu et al., 2007 ; Marchetto et al., 2011 ; Shi et al., 2017a ; Li et al., 2018a ; Li and Shi, 2020 ). In response to the COVID-19 pandemic, hiPSC-derived NPCs, neurons, and brain organoids have been used to model SARS-CoV-2 neurotropism ( Jacob et al., 2020 ; Mesci et al., 2020 ; Pellegrini et al., 2020 ; Ramani et al., 2020 ; Song et al., 2020 ; Zhang et al., 2020 ). These studies all reported infection of neurons and/or astrocytes by SARS-CoV-2; however, different extents of infection have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These studies all reported infection of neurons and/or astrocytes by SARS-CoV-2; however, different extents of infection have been reported. Some reported sparse infection of neurons and astrocytes ( Jacob et al., 2020 ; Pellegrini et al., 2020 ), whereas others showed more extensive infection of these cell types in either 2D or 3D cultures ( Mesci et al., 2020 ; Ramani et al., 2020 ; Song et al., 2020 ; Zhang et al., 2020 ). The cause for this discrepancy remains to be explored.…”
Section: Introductionmentioning
confidence: 99%